Synthesis of Near-Fault Ground Motion Using a Hybrid Method of Stochastic and Theoretical Green’s Functions - Wu, Shuang Lan; Charatpangoon, Bhuddarak; Kiyono, Junji; Maeda, Yoshito; Nakatani, Takao; Li, Shou Yi (Frontiers in Built Environment, 2016)
The effect of near-fault ground displacement is a significant factor when structures straddle a fault, because the fault produces both static step-like deformations and dynamic pulse-like ground motions. It has been observed that the static displacements measured up to 10 m and strong ground motion velocity pulses exceed 100 cm/s. As there is no concrete method for the seismic design of near-fault structures based on earthquake-induced fault displacement, the numerical simulation of near-fault ground motions is of great significance. In this paper, we describe a hybrid method combining stochastic and theoretical Green’s functions for synthesizing near-fault ground motions. Our approach considers the complete waveforms (far-, intermediate-, and near-field terms) of both the dynamic and static terms. To demonstrate the hybrid method, two simple examples of strike-slip and dip-slip fault models are simulated. The results exhibited dynamic displacement with the fling-step of near-fault movement. Furthermore, the 1999 Chi-Chi earthquake in Taiwan is also simulated, and the results showed good agreement with the observed recordings. Thus, the proposed method is a useful tool for evaluating near-fault ground motions for designing bridges and other structures.